2022
DOI: 10.1016/j.jbc.2021.101529
|View full text |Cite
|
Sign up to set email alerts
|

Efficient incorporation and template-dependent polymerase inhibition are major determinants for the broad-spectrum antiviral activity of remdesivir

Abstract: Remdesivir (RDV) is a direct-acting antiviral agent that is approved in several countries for the treatment of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). RDV exhibits broad-spectrum antiviral activity against positive-sense RNA viruses, e.g., SARS-CoV-2 and hepatitis C virus (HCV), and non-segmented negative-sense RNA viruses, e.g., Nipah virus (NiV), while segmented negative-sense RNA viruses such as influenza (Flu) virus or Crimean-Congo he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 59 publications
(128 reference statements)
0
41
0
Order By: Relevance
“…However, increases in nucleoside-triphosphate (NTP) concentrations can overcome this obstacle and RNA synthesis can continue, resulting in RNA strands with incorporated RDV-monophosphate (RDV-MP) residues. In this setting, template-dependent inhibition of RNA synthesis occurs because of compromised incorporation of the complementary uridine-triphosphate (UTP) opposite RDV-MP ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, increases in nucleoside-triphosphate (NTP) concentrations can overcome this obstacle and RNA synthesis can continue, resulting in RNA strands with incorporated RDV-monophosphate (RDV-MP) residues. In this setting, template-dependent inhibition of RNA synthesis occurs because of compromised incorporation of the complementary uridine-triphosphate (UTP) opposite RDV-MP ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, a structure of the preincorporated state of RDV-TP in the RdRp active site is still unavailable. We built a model, described previously ( 14 , 15 , 36 ), based on an existing structure of the polymerase complex, Nsp12/(Nsp8) 2 /Nsp7/(Nsp13) 2 , with primer and template RNA (PDB no. 6XEZ ) ( 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that the RdRp of SARS-CoV-2 incorporated the pharmacologically active RDV triphosphate (RDV-TP) species approximately three-fold more efficiently than its natural counterpart ATP [14]. Moreover, the biochemical evaluation of viral RdRp from different RNA viruses demonstrated efficient RDV-TP incorporation is required to elicit an antiviral effect [15]. To address the differences observed in the antiviral activity of TFV-DP and FTC-TP against SARS-CoV-2, we determined the efficiency at which the NRTIs were incorporated by SARS-CoV-2 RdRp (Table 3).…”
Section: Tfv-dp and Ftc-tp Are Poor Substrates Of Sars-cov-2 Rdrpmentioning
confidence: 99%
“…The pFastBac-1 (Invitrogen, Burlington, ON, Canada) plasmid with the codon-optimized synthetic DNA sequences (GenScript, Piscataway, NJ, USA) coding for SARS-CoV-2 (NCBI: QHD43415.1) nsp5, nsp7, nsp8, and nsp12 were used as a starting material for protein expression in insect cells (Sf9, Invitrogen, Waltham, MA, USA) [14,15]. We employed the MultiBac (Geneva Biotech, Indianapolis, IN, USA) system for protein expression in insect cells (Sf9, Invitrogen) according to published protocols [30,31].…”
Section: Biochemical Assays 451 Sars-cov-2 Rdrp Expression and Purifi...mentioning
confidence: 99%